Theoretical and Practical Significance of the Issue of Maritime Delimitation in the Law of the Sea - Lakićević-Đuranović, Bojana (Transactions on Maritime Science, 2017)
This paper aims to show the significance of maritime delimitation in the Law of the Sea, as well as the contribution of international jurisprudence to the creation of the rules of maritime delimitation. The decisions of the International Court of Justice (ICJ) and the awards of arbitration tribunals are especially significant in the part of the Law of the Sea dealing with maritime delimitation. Based on the analysis of the principle of equity and the method of equidistance, the jurisprudence of the courts is shown to have established precedents and to have an irreplaceable role in the development of the international Law of the Sea, particularly in the segment of maritime delimitations.